(untitled) (Biological Sciences - PJSIR, 1994)
The preferential ex.traction of copper from a multi component feed is achieved by using kerosene solution of di-(2-ethylhexyl) phosphoric acid. The extraction of metal has been found tobe influenced by both distribution constant and dissociation constant of the metal species involved. The theoretical predictions were confirmed experimentally by employing multistage extraction unit.